Peculiarities of immunohistochemical differential diagnosis of benign prostatic hyperplasia, intraepithelial neoplasia and prostate cancer. - Tumanskiy, V. A.; Popovich, A. A.; Popovich, S. A.; Tumanskaja, L. M. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. According to global statistics prostate cancer (РС) is the second leading cause of death and takes the second place in males cancer structure. Objective. Trephine biopsies of 32 patients with acinar РС and 30 patients with benign prostatic hyperplasia (BPH), which in 22 patients were combined with multifocal prostatic intraepithelial neoplasia (PIN) were studied. Methods. Immunohistochemical method was used to determine the expression of high molecular weight cytokeratin (CK HMW), alpha-methylacetyl-CoA racemase (AMACR/p504s) and androgen receptors. Results. Immunohistochemical differential feature of BPH is the presence in basal glands CK HMW-positive cells and lack of cytoplasmic expression of AMACR/p504s in secretory gland cells. Tufting, micropapillary and cribriform high-grade PIN differs from acinar PC by the presence of basal CK HMW-positive cells in the proliferative atypical epithelial-luminal cells and the absence in the last one of cytoplasmic expression of AMACR/p504s. Acinar PC is characterized by the absence of basal NMW CK-positive tumor cells in the cancer acini, cytoplasmic expression of AMACR/ p504s in malignant epithelial cells. Nuclear expression of androgen receptors are defined in the epithelium cells of acini and fibromuscular stroma of prostate, as well as in malignant PC acinar cells. Conclusion. The absence in acinar structures of CK HMW-positive basal cells and presence of AMACR/p504s-positive tumor cells in trephine biopsy of prostate give the possibility to authentically determine acinar PC and differentiate it from high-grade PIN and from different subtypes of BPH.